Hospital outcomes and cumulative burden from complications in type 2 diabetic sepsis patients: a cohort study using administrative and hospital-based databases. (September 2019) - Hsieh, Ming-Shun; Hu, Sung-Yuan; How, Chorng-Kuang; Seak, Chen-June; Hsieh, Vivian Chia-Rong; Lin, Jin-Wei; Chen, Pau-Chung
Background: The association between type 2 diabetes and hospital outcomes of sepsis remains controversial when severity of diabetes is not taken into consideration. We examined this association using nationwide and hospital-based databases. Methods: The first part of this study was mainly conducted using a nationwide database, which included 1.6 million type 2 diabetic patients. The diabetic complication burden was evaluated using the adapted Diabetes Complications Severity Index score (aDCSI score). In the second part, we used laboratory data from a distinct hospital-based database to make comparisons using regression analyses. Results: The nationwide study included 19, 719 type 2 diabetic sepsis patients and an equal number of nondiabetic sepsis patients. The diabetic sepsis patients had an increased odds ratio (OR) of 1.14 (95% confidence interval 1.1–1.19) for hospital mortality. The OR for mortality increased as the complication burden increased [aDCSI scores of 0, 1, 2, 3, 4, and ⩾5 with ORs of 0.91, 0.87, 1.14, 1.25, 1.56, and 1.77 for mortality, respectively (all p  < 0.001)]. The hospital-based database included 1054 diabetic sepsis patients. Initial blood glucose levels did not differ significantly between the surviving and deceased diabetic sepsis patients: 273.9 ± 180.3 versus 266.1 ± 200.2 mg/dl ( p  = 0.095). Moreover, the surviving diabetic sepsis patients did not have lower glycated hemoglobin (HbA1c; %) values than the deceased patients: 8.4 ± 2.6 versus 8.0 ± 2.5 ( p  = 0.078). Conclusions: For type 2 diabetic sepsis patients, the diabetes-related complication burden was the major determinant of hospital mortality rather than diabetes per se, HbA1c level, or initial blood glucose level.